Caratteristiche della flora vascolare pugliese - Marchiori S.; Medagli P.; Mele C.; Scandura S.; Albano A. (La cooperazione italo-albanese per la valorizzazione della biodiversità, 2000)
An assessment has been carried put, on the basis of bibliographical and experimental data, of the quality and quantity of the flora of Apulia. 2075 sub-generic taxa have been registered, arranged in 128 families and 707 genera. The most representative families are: Compositae with 230 species, Leguminosae with 213, Gramineae with 209, while the most common genera are Trifolium with 40 species, Vicia with 32, Ranunculus with 30, Allium with 26, Euphorbia with 25. As for the life forms, there is a prevalence of Therophytes with 790, followed by Hemicryptophytes with 616, Geophytes with 302, Chamaephytes with 149, Phanerophytes with 116, Nanophanerophytes with 59, Hydrophytes with 38 and Helophytes with 5. Chorologically speaking, there is a clear prevalence of stenomediterranean species (31.37percent), followed by Eurasian species (20.1percent), Euromediterranean (17.64percent) widespread species (8.55percent), Mediterranean mountain species (3.04percent), boreal species (4.92percent), endemic species (4.48percent), exotic species (3.57percent), Atlantic species (3.71percent), steppe species (3.33percent) and, finally, orophile species (1.3percent).
Seminario: La Cooperazione Italo-Albanese per la Valorizzazione della Biodiversità, 2000/02/24-26, Lecce (Italy)